Metal resources and energy - Chapman, P. F. (Butterworths monographs in materials., 1983)
Metal Resources and Energy was initially aimed at exploring the future availability of metals and the energy required to produce them. During the detailed planning of the book, the authors decided to extend the remit to consider fuel use in relation to resources and future availability. In order to explore this relationship a framework was established which provided an agenda of topics to examine. In the process of systematically working through this agenda a deeper understanding of resource issues and some new insights were obtained. This book develops a framework for assessing the future ava.